Electron and gamma irradiation effects on Al/n‒4H–SiC Schottky contacts. (February 2020) - Vali, Indudhar Panduranga; Shetty, Pramoda Kumara; Mahesha, M.G.; Petwal, V.C.; Dwivedi, Jishnu; Phase, D.M.; Choudhary, R.J.
Abstract: The Al/n‒4H–SiC Schottky contacts were prepared and studied their contact properties by current‒voltage ( I − V ) characteristics and X‒ray photoelectron spectroscopy (XPS) technique. The results have shown localized Fermi‒level pinning (FLP) due to grown‒in defects in n‒4H–SiC. The electron and gamma irradiation on Schottky contacts have shown zero‒bias offset in the I − V characteristics. The XPS studies revealed that the observed behaviour was mainly attributed to irradiation‒induced defects in n‒4H–SiC bulk and their role in tunneling mechanism rather than contribution from the surface or interface chemical features alone. Highlights: Pristine Al/n‒4H–SiC Schottky contacts showed inhomogeneous nature of Φ B as well as localized FLP . A wide discrepancy in the Φ B for different N D has been attributed to the presence of different grown‒in defect states. Zero‒bias offset in the I–V characteristics of irradiated Schottky contacts is attributed to irradiation‒induced defects.